Legal Certainty of Regulations on the Obligation to Notify the Minister Regarding Legal Status of Fiduciary Collateral - Meidiana Indah Lestari; Reka Dewantara; Mohammad Hamidi Masykur (Faculty of Law, University of Jember, Indonesia, 2025)
The Fiduciary Guarantee aims to provide legal certainty for the parties involved; however, inconsistencies and ambiguities in its regulatory framework create contradictions regarding legal certainty. Law No. 42 of 1999, Government Regulation No. 21 of 2015, and Minister of Law and Human Rights Regulation No. 25 of 2021 fail to consistently regulate the obligation to remove fiduciary guarantees and do not provide legal certainty regarding the status of fiduciary objects if their removal is delayed beyond 14 days. This lack of clarity has the potential to harm the public, particularly fiduciary grantors who have fulfilled their obligations but face obstacles in the guarantee removal process. Furthermore, the incomplete regulation on fiduciary removal leads to legal uncertainty. This study examines the Juridical Implications of the Regulation on the